2008
DOI: 10.1177/0959683608095575
|View full text |Cite
|
Sign up to set email alerts
|

A 700-year history of groundwater recharge in the drylands of NW China

Abstract: A 700-year semi-quantitative history of diffuse groundwater recharge in the Badain Jaran Desert (Inner Mongolia) is proposed on the basis of solute data from multiple unsaturated zone groundwater profiles using mass balance of chloride to establish recharge rates and profile chronologies. Four relatively humid (1330—1430, 1500—1620, 1700—1780 and 1950—1990) and three relatively arid phases (1430—1500, 1620—1700 and 1900—1950) are discernable across the profiles. The recharge history broadly reflects multidecad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 49 publications
3
38
1
Order By: Relevance
“…Recharge rates from the arid western sites in the Thar Desert are consistent with recharge estimates from similar regions globally, including those in the Badain Jaran desert in N. China with predominantly Asian summer monsoon precipitation (CMB recharge, 1.4 mm/year; 1.7% of MAP (84 mm/year; Gates et al 2008). In contrast, there is no recharge in (semi)arid regions in perennially vegetated, semiarid regions in the southwestern USA, based on Cl and pressure data (Phillips 1994), or in revegetated areas of the Tengger Desert (China), based on lysimeter monitoring (1990)(1991)(1992)(1993)(1994)(1995)-MAP 174 mm/year (Wang et al 2004).…”
Section: Comparison With Recharge Estimates From Previous Studiessupporting
confidence: 75%
See 1 more Smart Citation
“…Recharge rates from the arid western sites in the Thar Desert are consistent with recharge estimates from similar regions globally, including those in the Badain Jaran desert in N. China with predominantly Asian summer monsoon precipitation (CMB recharge, 1.4 mm/year; 1.7% of MAP (84 mm/year; Gates et al 2008). In contrast, there is no recharge in (semi)arid regions in perennially vegetated, semiarid regions in the southwestern USA, based on Cl and pressure data (Phillips 1994), or in revegetated areas of the Tengger Desert (China), based on lysimeter monitoring (1990)(1991)(1992)(1993)(1994)(1995)-MAP 174 mm/year (Wang et al 2004).…”
Section: Comparison With Recharge Estimates From Previous Studiessupporting
confidence: 75%
“…The hydrostratigraphic records trace past changes in recharge in response to variations in forcing from land-use change and climate variability (Scanlon et al , 2007aGates et al 2008;Favreau et al 2009). Unsaturated zone pore water NO 3 concentrations provide information on whether there is natural NO 3 in the profile from atmospheric deposition, as found in parts of the southwestern USA (Walvoord et al 2003), from nitrogen fixation by native vegetation, as found in Senegal (Deans et al 2005), or from mineralization and nitrification of soil organic nitrogen and over application and leaching of applied fertilizers in cropland areas (Scanlon et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is vital to understand the processes and rates of groundwater recharge to utilize and manage groundwater resources sustainably. In arid and semi-arid regions unsaturated zones have been recognized as possible sources that retain information on such relations (Stone 1992;De Vries et al 2000;Gates et al 2008). This is because water flow is slow and mixing processes are often small in arid and semi-arid environment unsaturated zones.…”
Section: Introductionmentioning
confidence: 99%
“…The chloride profile in the unsaturated zone can also be used to reveal the palaeoclimate changes. Palaeoclimate and palaeohydrology archives at different time scales have been achieved from vadose-zone chloride profiles in arid and semi-arid areas around the world (Edmunds and Walton 1980;Cook et al 1992;Tyler et al 1996;Gates et al 2008). For example, using the CMB method, Cook et al (1992) reconstructed the history of unsaturated zone recharge over the past 400-year at northern Senegal, which can be matched with the rainfall and lake level records, implying that the chloride profile can be used to infer the palaeoclimate variations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation